Violence studies - Kannabirān, Kalpana; Council for Social Development (India). Southern Regional Centre, Hyderabad; International Conference on Violence and Its Habitations in India (2013 : Hyderabad, India) (New Delhi, India : Oxford University Press, 2016)
Includes selected papers presented at an International Conference on Violence and Its Habitations in India organized by Council for Social Development, Hyderabad from 28 to 30 November, 2013.
Includes bibliographical references and index.
Keywords: Political violence -- India; Caste -- Political aspects -- India; Women -- Violence against -- India